Agrippina : mother of Nero - Barrett, Anthony, 1941- (Batsford, 1996)
"Villains, not saints, are the usual stuff of legends, establishing themselves permanently in popular lore and imagination. There are fiends whose villainies are so colourful, so sinister that they both repel and fascinate. Agrippina the Younger is one such, having attained a level of power unprecedented for a woman in first century Rome by a combination of sexual exploitation and ruthless murder. She was so powerful that, after her death, no woman within the imperial family dared overtly assume a major role in political affairs for some 150 years. The ancient sources believed Agrippina plotted against her brother, murdered her husband (the emperor) and slept with her son in order to control him. But did she?" "In this dynamic new biography - the first on Agrippina in English - Professor Barrett uses the latest archaeological, numismatic and historical evidence to provide a close and detailed study of her life and career. He shows how Agrippina's political contribution to her time seems in fact to have been positive, and that when she is judged by her achievements she demands admiration. Revealing the true figure behind the propaganda and the political machinations of which she was capable, he assesses the impact of her marriage to the emperor Claudius, on the country and her family. Finally, he exposes her one real failing - her relationship with her son, the monster of her own making to whom, in horrific and violent circumstances, she would eventually fall victim."--Jacket